Viral Marketing Dynamics and Consumer Behavior in the Digital Age: A Systematic Literature Review - Musael Nur Aziza; Ratih Hurriyati; Puspo Dewi Dirgantari (Sinergi International Journal of Management and Business, 2026)
Viral marketing has evolved from traditional word-of-mouth into a complex ecosystem shaped by algorithms, artificial intelligence, psychological mechanisms, and cross-platform interactions. This study synthesizes empirical findings from 2015–2025 to identify the cognitive, affective, and technological determinants influencing viral marketing effectiveness across multiple industries. Unlike prior reviews that primarily emphasized emotional triggers or structural network mechanisms, this study integrates technological, cognitive, and affective dimensions within a PRISMA-2020-guided Systematic Literature Review (SLR). Using Scopus as the primary database, complemented by metadata extraction through the Watase UAKE tool, a total of 34 peer-reviewed journal articles were analyzed. Findings reveal three key dimensions: (1) cognitive mechanisms such as credibility judgment and information diagnosticity; (2) affective triggers involving emotional arousal that shapes sharing and engagement; and (3) technological enablers including AI-driven seed targeting, optimization algorithms, and budget allocation models. The results highlight that viral marketing success emerges from the interaction between emotional activation, cognitive evaluation, and algorithmic amplification. Future research should explore cross-platform diffusion, ethical concerns regarding AI-personalization, and long-term consumer behavioral trajectories.